2013
DOI: 10.1179/1743132813y.0000000225
|View full text |Cite
|
Sign up to set email alerts
|

The curry spice curcumin attenuates beta-amyloid-induced toxicity through beta-catenin and PI3K signaling in rat organotypic hippocampal slice culture

Abstract: These results reinforce the neuroprotective effects of curcumin on Abeta toxicity and add some evidence that its mechanism may involve beta-catenin and PI3K signaling pathway in organotypic hippocampal slice culture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Curcumin has been recognized as an effective agent for neurodegenerative diseases, because of its neuroprotective effects in PD, AD, and ALS [45]. Curcumin also ameliorates neurotoxicity induced by various toxicants such as metals (fluoride, lead, and arsenic), solvents, 6-OHDA, and Aβ [36,37,[40][41][42][43][44]. Recently, we found that curcumin enhanced the adult hippocampal neurogenesis as well as improved learning and memory deficits in AD model via recruitment of the Wnt/β-catenin pathway [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Curcumin has been recognized as an effective agent for neurodegenerative diseases, because of its neuroprotective effects in PD, AD, and ALS [45]. Curcumin also ameliorates neurotoxicity induced by various toxicants such as metals (fluoride, lead, and arsenic), solvents, 6-OHDA, and Aβ [36,37,[40][41][42][43][44]. Recently, we found that curcumin enhanced the adult hippocampal neurogenesis as well as improved learning and memory deficits in AD model via recruitment of the Wnt/β-catenin pathway [41].…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin attenuates neurotoxicity induced by various toxicants such as fluoride, acrolein, okadaic acid, lead, ethanol, arsenic, sodium metabisulfite, 6-hydroxydopamine (6-OHDA), and amyloid-β (Aβ) [34][35][36][37][38][39][40][41][42][43][44]. Curcumin also provides neuroprotection in cellular and animal models of neurological and neurodegenerative disorders including Parkinson's disease (PD), Alzheimer's disease (AD), Huntington's disease (HD), depression, multiple sclerosis, and schizophrenia [45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…However, the role of Akt-GSK3β in regulating OS-induced osteoblast apoptosis is unknown. Furthermore, studies have indicated that curcumin exerts a protective effect against apoptosis via the phosphoinositide 3-kinase (PI3K)/Akt signaling pathway [32,33]. However, whether curcumin treatment promotes osteoblast survival through prevention of OS-induced mitochondrial dysfunction and activation of Akt-GSK3β signaling remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Curcumin, which is extracted from Curcuma longa L, has been shown to exert a range of pharmacological effects, including antioxidative and anti-inflammatory activity, which may be useful for preventing cancer. [10][11][12] Curcumin can also reduce infarct volume and improve neurological function after middle cerebral artery occlusion (MCAO), [13][14][15][16] leading us to wonder whether curcumin may promote proliferation and differentiation of NSCs after stroke. Indeed, studies have shown that curcumin can influence proliferation and differentiation of nerve cells, 17,18 though whether this is also true in ischemic animals is unknown.…”
Section: Introductionmentioning
confidence: 99%